2015
DOI: 10.1007/s10295-015-1697-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of enzymatic apple pomace hydrolysate to production of 2,3-butanediol by alkaliphilic Bacillus licheniformis NCIMB 8059

Abstract: 2,3-Butanediol (2,3-BD) synthesis by a nonpathogenic bacterium Bacillus licheniformis NCIMB 8059 from enzymatic hydrolysate of depectinized apple pomace and its blend with glucose was studied. In shake flasks, the maximum diol concentration in fed-batch fermentations was 113 g/L (in 163 h, from the hydrolysate, feedings with glucose) while in batch processes it was around 27 g/L (in 32 h, from the hydrolysate and glucose blend). Fed-batch fermentations in the 0.75 and 30 L fermenters yielded 87.71 g/L 2,3-BD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Jiang et al cultivated Paenibacillus polymyxa CICC 10010, in an enzymatic hydrolysate of microcrystalline cellulose with glucose concentrations of approximately 100 g/L, cultivated at 30°C and 200 rpm, obtaining a maximum 2,3‐BD production of 40 g/L and productivity of 0.70 g/(L/h). Białkowska et al used the enzymatic hydrolysate of apple pomace (approximately 43 g/L of glucose) to cultivate Bacillus licheniformis NCIMB 8059, under conditions of 37°C and 130 rpm in shake flask batch fermentations, obtaining 2,3‐BD yields of 0.36 g/g and productivity of 0.66 g/(L/h). When the authors used the same medium, but running a fed‐batch cultivation, the production was up to 113 g/L of 2.3‐BD.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al cultivated Paenibacillus polymyxa CICC 10010, in an enzymatic hydrolysate of microcrystalline cellulose with glucose concentrations of approximately 100 g/L, cultivated at 30°C and 200 rpm, obtaining a maximum 2,3‐BD production of 40 g/L and productivity of 0.70 g/(L/h). Białkowska et al used the enzymatic hydrolysate of apple pomace (approximately 43 g/L of glucose) to cultivate Bacillus licheniformis NCIMB 8059, under conditions of 37°C and 130 rpm in shake flask batch fermentations, obtaining 2,3‐BD yields of 0.36 g/g and productivity of 0.66 g/(L/h). When the authors used the same medium, but running a fed‐batch cultivation, the production was up to 113 g/L of 2.3‐BD.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, genetic engineering to decrease by-product formation and to enable production of optically pure 2,3-butanediol will be beneficial [12, 51, 52]. Furthermore, the cultivation medium has to be optimized with respect to utilization of cheaper carbon sources and media components [18, 23, 30, 53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Although the sugar consumption rate slowed down in the initial 12 h and the overall 2,3-BDO productivity decreased, the 2,3-BDO yield from each gram sugar was not jeopardized by decreasing yeast extract and peptone concentrations. Compared to the glucose media, the food waste and its hydrolysate usually contain substances such as minerals and vitamins which are essential nutrients for microbial 2,3-BDO production [ 31 ]. Jurchescu et al (2013) reported a high production of 2,3-BDO using a rich media with various macro- and micro-elements in addition to glucose [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jurchescu et al (2013) reported a high production of 2,3-BDO using a rich media with various macro- and micro-elements in addition to glucose [ 32 ]. B. licheniformis NCIMB 8059, the strain investigated in the study of Białkowska et al (2015), could not consume any glucose or fructose to produce 2,3-BDO without adding a mineral mixture [ 31 ]. However, when using enzymatic apple pomace hydrolysate (10 g/L) as the media, the yield of 2,3-BDO reached as high as 0.47 g/g.…”
Section: Resultsmentioning
confidence: 99%